Grain boundary–slip bands interactions: Impact on the fatigue crack initiation in a polycrystalline forged Ni-based superalloy. (15th October 2015) - Larrouy, Baptiste; Villechaise, Patrick; Cormier, Jonathan; Berteaux, Olivier
Graphical abstract: Abstract: Low cycle fatigue properties of polycrystalline γ–γ′ Ni-based superalloys are dependent on many factors such as temperature, environment, grain size and distribution of the strengthening phases. Under LCF conditions, an intergranular crack initiation is often observed. The local conditions favoring such a damage mode are analyzed in this paper considering the high strength cast and wrought Udimet™ 720Li alloy tested at room temperature. Tensile and fatigue tests were performed on samples having two different microstructures with various γ′ precipitates distributions. The objective is to focus on the plasticity and damage processes developed near grain boundaries. A special attention was paid on the slip transfer between neighboring grains taking into account the local crystallographic orientations. In some specific crystallographic configurations (linked to geometrical considerations between slip planes activated on both side of the grain boundary), a localized crystallographic rotation was detected within very small volumes confined at the tip of slip bands developed in the neighboring grain. Although limited in size (∼30 μm 3 ), these micro-volumes are associated to an intense elastic/plastic activity resulting from very high local stresses due to the elastic rotations. The development of such specific zones was investigated at different stages of the monotonic and cyclic behavior at room temperature and was identified as favoring micro-cracks initiation.